School climate and creativity as predictors of psychological resilience among college students - Yan, Yu; Li, RongHua (Frontiers in Psychiatry, 2025)
BackgroundThe overuse of smartphones prevails in college that strongly links to poor school climate, and brings great academic and psychological challenges to college students despite promotion in convenience of life and study. While moderate negative emotions caused by school climate can enhance creativity and further foster psychological resilience, severe adverse effects would impede development of resilience.MethodsThis study aims to examine the prediction of four factors (school climate, creativity, social anxiety and sense of place) on psychological resilience by developing a prediction model based on the decision tree algorithm. The analysis was conducted in Modeler 18.0 with C5.0 algorithm, and the model accuracy is 78.26%. A sample of 607 college students participated, completing five established scales: Connor-Davidson Resilience Scale, Runco Ideational Behavior Scale, Perceived School Climate Scale, Social Anxiety Subscale of the Self-Consciousness Scale and Sense of Place Scale.ResultsPsychological resilience was predicted by four factors, in order of significance: creativity, school climate, social anxiety and sense of place. Additionally, creativity emerged as the most significant predictor of psychological resilience with a notable margin over the other three factors.ImplicationsThis study offers valuable insights for researchers to understand predictive relationships and capabilities of creativity and school climate on psychological resilience, provides a tool for school to identify, anticipate and decrease students’ psychological crisis, and further contributes to designing targeted development and management programs that enhance mental health support for students.